Analisis Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Padi Sawah Varietas Inpari 45 - Baihaqi syahputra; M. Nasir Ismail; Syarifuddin Syarifuddin; Teuku Fadhla (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Farming is a science that studies how a person allocates existing resources effectively and efficiently to obtain high profits at a certain time. The aim of this research is to determine the effect of land area, seeds, labor, urea fertilizer, NPK fertilizer, TSP fertilizer and pesticides on the production of lowland rice of the Inpari 45 variety in Lam Seunong Cot Keueung Village, Kuta Baro District, Aceh Besar Regency. The research method used was a survey method. The sampling technique "simple random sampling" was 30% with a sample size of 24 farmers. The data analysis method used in this research is multiple linear regression analysis. Simultaneous test results (f test) show that land area, seeds, labor for urea fertilizer, NPK fertilizer, TSP fertilizer and pesticides. Simultaneously, it has a real effect on the production of lowland rice of the Impari 45 variety because f cari > f table. Meanwhile, the Parsiar test (t test) shows that seeds, urea fertilizer and pesticides have a significant effect on the production of lowland rice of the Inpari 45 variety because tcari > t table. Meanwhile, land area, labor, NPK fertilizer and TSP fertilizer do not have a significant effect on the production of lowland rice of the Inpari 45 variety because tcari < t table.